(3GdHOjYs - (3GSGeI Hf efbP , GSGeI Hf eQTO Hf Ydj Hf ebdO Hf fUQ Hf efbP GdcfGfj GdcdHj, CHh GdeXaQ,J (B584 (3g` s
(3BNQgG (B:s
(3HYV GdcdGe Ydi GdJgPjH hGdJQJjH s
(3GdfSNI HgG MhGTs
(3eQJH Ydi (B95 (3HGHkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B19 - (3U (B406 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B235s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs